PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIKKELAS VII-4SMP NEGERI21 PEKANBARU - Welni Anugrah Lestari; Jalinus Jalinus; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This research is a class action research which aimedto improve learning process and increase the mathematicslearning outcomesby implying Problem Based Learning model. The subjects of this research wereVII-4grade student’s of SMPNegeri21Pekanbaru in the academic year 2019/2020. The total number of participants were40students, consisting of 18male students and 22 female students with heterogeneous academic achievement. This research tooktwo cycles,in which each cycle consisted of four stages: planning, implementation, observation, and reflection. Each cycles endedwithdaily examination. The data collected by observation and test. The datawereanalyzedby narative descriptiveand statistical descriptive.The data wereobtained fromthe observation sheetsshows that teacher and studentsactivitieswereimprovedafter the modelimplemented. From the data of studentsevaluation test, shows that the percentage of students who passed minimal mastery learningincreased from the basic score before action (10%)to at the first test (27,5%).Students learning outcomes also increased from the first testto the second test(55%).Based on the explanation above the implementation ofProblem BasedLearning model couldimprove the learning process and increasethemathematicslearning otcomesfrom students of grade VII-4SMP Negeri 21Pekanbaruon odd semester of 2019/2020ofthe subject matter algebraic form.KeyWords:MathematicsLearning Achievement, Problem Based LearningModel,ClassroomActionResearch.